PALEOPROTEROZOIC GABBROANORTHOSITES OF THE SELENGA-STANOVOI SUPERTERRANE, SOUTHERN FRAMING OF THE SIBERIAN CRATON - Buchko I.V.; Larin A.M.; Velikoslavinskii S.D.; Sorokin A.A.; Sal'nikova E.B.; Kotov A.B.; Sorokin A.P.; Yakovleva S.Z. (My University, 2006)
The Selenga–Stanovoi Superterrane of the southern framing of the Siberian Craton includes numerous layered different (in genesis and composition) ultramaficmafic and gabbroanorthosite massifs (Kengurak–Sergachi, Lukinda, Nyukzhin, Veselki, and others). Their place in the geological evolution of the region is a much-debated problem. Previously, these massifs together with host granitoids and metamorphic rocks were ascribed to the Early or Late Precambrian. Recent isotope data indicate a younger age of many magmatic complexes in the southern framing of the Siberian Craton, including some ultramafic–mafic massifs, which were previously considered Precambrian structures.
Keywords: Selenga–Stanovoi superterrane; Siberian craton; Paleoproterozoic; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская